ANALISIS PENGELOLAAN LIMBAH PADAT MEDIS DI RUMAH SAKIT dr. KANUJOSO DJATIWIBOWO BALIKPAPAN - Mulya, Widya; Rusba, Komeyni; Zulfikar, Iwan; Agus, Agus (IDENTIFIKASI, 2022)
Hospitals are health institutions that have many installations and are never separated from the generation of solid waste (medical and non-medical) hospitals. Hospital activities will produce a number of by-products, both solid, liquid and gaseous waste containing pathogens, chemicals and generally dangerous and dangerous medical devices. The purpose of this study was to analyze the medical waste management system at Dr. Hospital. Kanujoso Djatiwibowo Balikpapan Year 2020, Identification of hazardous waste characteristics at each waste source at Dr. Hospital. Kanujoso Djatiwibowo Balikpapan with existing standards. Based on the Decree of the Minister of Health of the Republic of Indonesia Number 1204 of 2004 concerning Hospital Environmental Health, waste management can be carried out by minimizing waste by reducing materials, reusing and recycling, sorting and storing medical and non-medical waste. , collection with strong and closed trolleys and processing waste to be safe before being discharged into the environment, Regulation of the Minister of Environment and Forestry Number: P.56/Menlhk-Setjen/2015 concerning Procedures and Technical Requirements for Management of Hazardous and Toxic Waste from Facilities Health services. This research is a qualitative research with qualitative methods. The data collection used checklist, observation, and in-depth interviews, while the data analysis was processed using qualitative techniques to describe the efforts to manage medical solid waste at Dr. Hospital. Kanujoso Djatiwibowo Balikpapan which is then compared with the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.56/Menlhk-Setjen/2015 concerning Procedures and Technical Requirements for Management of Hazardous and Toxic Waste from Health Service Facilities. The results showed that Dr. Hospital. Kanujosos Djatiwibowo Balikpapan is in accordance with the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.56/Menlhk-Setjen/2015. Based on the results of the percentage tabulation, it is known that the management of medical waste at Dr. Hospital. Kanujoso Djatiwibowo Balikpapan, which is as much as 72.22% in accordance with the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number: P.56/Menlhk-Setjen/2015 while it is known that 27.78 are not appropriate.